2013
DOI: 10.1108/jd-01-2012-0001
|View full text |Cite
|
Sign up to set email alerts
|

Towards a conceptual framework for provider information behaviour

Abstract: Purpose -The purpose of this paper is to provide a critical discussion of the paucity of research on information behaviour of information providers and to propose a framework for investigating the emerging area of provider information behaviour. Design/methodology/approach -The approach takes the form of a conceptual analysis and literature review.Findings -A multidisciplinary framework is provided to form the basis of further exploration of provider information behaviour.Research limitations/implications -The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 96 publications
(139 reference statements)
0
7
0
Order By: Relevance
“…Information seeking is the process of attempting to acquire information from human and technological contexts using a specific database or information network [24]. Williamson and Asla [25] indicated that not all information seekers are alike and that they may vary according to various factors, including their gender, physical ability, and age.…”
Section: Information-seeking Processmentioning
confidence: 99%
“…Information seeking is the process of attempting to acquire information from human and technological contexts using a specific database or information network [24]. Williamson and Asla [25] indicated that not all information seekers are alike and that they may vary according to various factors, including their gender, physical ability, and age.…”
Section: Information-seeking Processmentioning
confidence: 99%
“…It would appear that, similarly to IL itself, there are issues surrounding the terminology used to describe frameworks. Davies and Williams (2013) developed a conceptual framework as a way of linking literature and research questions, and to inform research design. The resulting framework allowed for information providers to map individual and organizational information behaviour and aided in supporting understanding of internal information environments.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of proper information acquisition strategies at this phase leads to the failure of competitive intelligence. Information acquisition behavior is a type of information behavior and refers to information activities associated with getting information in response to an information need (Davies and Williams, 2013). The acquisition of information to meet information needs goes far beyond more information seeking, which is commonly used in the literature of LIS (Ikoja-Odongo and Ocholla, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The acquisition of information to meet information needs goes far beyond more information seeking, which is commonly used in the literature of LIS (Ikoja-Odongo and Ocholla, 2004). It includes information-seeking behavior, information finding behavior and information retrieval behavior (Davies and Williams, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation